2006
DOI: 10.2519/jospt.2006.2233
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes Following Manual Physical Therapy and Exercise for Hip Osteoarthritis: A Case Series

Abstract: Study Design: Case series describing the outcomes of individual patients with hip osteoarthritis treated with manual physical therapy and exercise. Case Description: Seven patients referred to physical therapy with hip osteoarthritis and/or hip pain were included in this case series. All patients were treated with manual physical therapy followed by exercises to maximize strength and range of motion. Six of 7 patients completed a Harris Hip Score at initial examination and discharge from physical therapy, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 56 publications
0
57
0
Order By: Relevance
“…The median might also be preferred over the mean when sample sizes are so small that they may not represent the target population. For example, in a case series including 7 patients with hip osteoarthritis, MacDonald et al 57 reported medians rather than means for all baseline attribute variables and for all outcome variables. If data are from nominal or ordinal scales, the mode or median scores, respectively, are reported to describe central tendency.…”
Section: Reporting Of Results In Treatment Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The median might also be preferred over the mean when sample sizes are so small that they may not represent the target population. For example, in a case series including 7 patients with hip osteoarthritis, MacDonald et al 57 reported medians rather than means for all baseline attribute variables and for all outcome variables. If data are from nominal or ordinal scales, the mode or median scores, respectively, are reported to describe central tendency.…”
Section: Reporting Of Results In Treatment Studiesmentioning
confidence: 99%
“…Clinicians may find it helpful to read one of the several case studies or case series where clinicians provide detailed description of applying current best evidence in managing patients with a variety of conditions. For example, MacDonald and colleagues 57 reported on the management of a series of patients with hip dysfunction who responded positively to novel manual therapy interventions. Similarly, Cleland et al 21 and Waldrop 82 have published case series that apply recently developed clinical prediction rules to patients.…”
Section: Step 5 Evaluating Perfor-mance On Steps 1 Throughmentioning
confidence: 99%
“…10 In clinical practice, joint mobilization techniques are commonly used to supplement therapeutic exercises for a multitude of conditions. 29 Specific to the shoulder, a systematic review published in 2003 9 studied the effect of manual therapy and therapeutic exercise on shoulder impingement syndrome. However, it also included studies that looked at the effects of physical agents and other medical interventions as primary inde- been treated with some type of mobilization and/or therapeutic exercise.…”
Section: T T Resultsmentioning
confidence: 99%
“…While there is research to support conservative treatment options for osteoarthritis at the hip 31,32,53 and knee, 17,18,94 evidence to support effective conservative treatment for individuals with posttraumatic ankle arthritis is lacking. There seem to be some indications that weight loss, the use of a cane for ambulation, bracing, and shoe wear modification should be included as part of a treatment program.…”
Section: Conclusion Pmentioning
confidence: 99%